OPERATION OF FLYING-CAPACITOR MODULAR MULTILEVEL CONVERTER WITH FOUR-WINDING COUPLED INDUCTORS - Luong, Van Tan; Dung, Le Duc; Quang, Huynh Nhat (HUIT Journal of Science, 2024)
In this paper, a coupled inductor with four windings for a flying-capacitor modular multilevel converter (FC-MMC) has been proposed to reduce the volume and weight of the magnetic component. In the conventional flying-capacitor MMC, four discrete inductors are needed to be assembled for a leg, however, these four inductors can be reduced to only one. By this, the volume of the magnetic core can be reduced by 47.3% and 8.2%, respectively, compared with the discrete and two-winding coupled inductors. The performance of the FC-MMC with the proposed coupled inductor has been shown by the simulation results.